The upward propagating ionospheric hiss waves during the seismic time observed by the China seismo-electromagnetic satellite - Lv, Fangxian; Hu, Yunpeng; Zhima, Zeren; Sun, Xiaoying; Lu, Chao; Yang, Dehe (Frontiers in Astronomy and Space Sciences, 2023)
The ionospheric hiss wave is a broadband incoherent and structureless electromagnetic emission. They appear in a relatively narrower frequency range between −0.1 and 1.5 kHz. However, according to previous observations, abnormal electromagnetic emissions during seismic activities also preferentially appear in the same frequency range of ionospheric hiss. This work studies the propagation features of the ionospheric hiss during seismic time based on the observations from the CSES (China Seismo-Electromagnetic Satellite). The wave vector analysis shows that during seismic activities, except for the downward propagating ionospheric hiss which is a common phenomenon in the ionosphere, there are upward propagating emissions mixed with the downward propagating ionospheric hiss. We made a statistical analysis of the shallow strong earthquakes (M ≥ 6.0, depth below 30 km) that occurred in mainland China from 2019 to 2022. We selected the ionospheric hiss events recorded by orbits passing over the epicenters within a time window (the 1-month prior to and 1-week after the main shock). We found that although most of the events are the typical downward propagating ionospheric hiss waves, however, there are certain events mixed with the upward propagating emissions. The statistical distribution analysis of wave propagation parameters shows that the major part of wave normal angles vary from 40 to 60, the azimuthal angles predominately attain below 40, and the ellipticity shows a more complicated feature varying around ± 0.5, and the planarity values predominate at values between 0.6 and 1. The frequency band of the upward propagating ionospheric hiss mostly varies between 300 Hz and 800 Hz. To further study the behavior of such upward propagating ionospheric hiss wave during the seismic time, we compared the wave activities under non-seismic activity and quiet space weather conditions, and the results confirm that the occurrence rate of the upward propagating emissions under quiet conditions is far less than that in the seismic time. We suggest that there is a link between the upward propagating ionospheric hiss and the seismic activity, but the physical reason behind it still remains a puzzle to us.